Using the Internet to support Libyan in-service EFL teachers' professional development - Elmabruk, Reda (2009)
Libyan in-service teachers of English with poor INSET provision and low-resourced school environments stand to gain a great deal from Internet-based Continuing Professional Development (I-CPD). The aim of this exploratory and descriptive study was threefold: first, to understand current practices and conditions pertaining to CPD provision for Libyan teachers; second, to explore the potential of Internet-based CPD for Libyan teachers through a bottom-up informal approach; third, to develop an I-CPD model appropriate for the Libyan context.